Quantitative assessment, stability, and cytotoxicity activity of GnRH-toxin conjugates - Yang, Wei-Hsiung, author; Nett, Terry M., advisor; Veeramachaneni, DN Rao, committee member; Clay, Colin M., committee member; Bowen, R. A., committee member; Burns, Patrick J., committee member (Colorado State University. Libraries, 2001)
Hormone-dependent cancers such as breast, endometrial, ovarian, and prostate cancers remain major diseases in America and throughout world. These cancers can be treated by surgical castration, sex steroid antagonists, and GnRH agonists or antagonists. However, these treatments have side effects and disadvantages. In view of non-specific toxicity of most chemotherapeutic agents against many normal cells, the development of targeted chemotherapy is warranted. Efficient targeting of chemotherapeutic drugs to the cancerous area could be of great benefit for patients with advanced or metastatic tumors. Pokeweed antiviral protein (PAP), a ribosome-inactivating protein, has potent antiviral activity or cytotoxic action against cells once inside the cytoplasm of both eukaryotes and prokaryotes. Ribonudease A (RNase), a distributive endoribonuclease, possesses cytotoxic activity, appears to facilitate host defenses by killing pathogens, and plays a physiological role in cell death. Therefore, PAP and RNase are good candidates for use as the cytotoxic component of hormonotoxins. Recently, a series of cytotoxic conjugates containing a gonadotropin-releasing hormone (GnRH) analog and PAP or RNase was developed. D-Lys6-GnRH-Pro9-ethylamide (D-Lys6-GnRH) was conjugated to PAP (GnRH-PAP) or RNase (GnRH-RNase) using a chemical cross-linking method. The biological effectiveness of a conjugate is dependent on stability and half-life in the circulation until it enters cells as well as its cytotoxicity once it enters the target cell. Therefore, a sensitive, specific, and accurate assay was needed to evaluate stability in biological fluids and circulating half-life. This assay must be able to distinguish both the toxin and targeting moieties of the conjugate to ensure that the substance being measured is the intact conjugate. Therefore, a sensitive sandwich enzyme-linked immunoabsorbent assay (ELISA) for GnRH-toxin conjugates was developed, using anti-GnRH to capture the conjugate and anti-PAP or anti-RNase for quantification. The data showed that conjugates prepared with disulfide-bond linker are easily degraded in sheep serum. However, a maleimidobutyryl-group linker is very stable in sheep serum. Thus, a non-cleavable linker should be considered for conjugates designed for use in vivo. The next objective was to determine if GnRH analog could be used as a cell-binding moiety to deliver PAP or RNase to cells expressing GnRH receptors. Chinese hamster ovary (CHO) cells that had been transfected with cDNA for the murine GnRH receptor to create a cell line expressing high levels of GnRH receptor and two mouse gonadotroph tumor cell lines that express endogenous GnRH receptors (αT3-1 and LβT2 cells) were used to evaluate the cytotoxic effects of GnRH-PAP and GnRH-RNase. Cytotoxicity of GnRH-PAP using human breast cancer, endometrial cancer, and prostate cancer cell lines was also examined. Treatment of GnRH receptor-positive cells with GnRH-PAP resulted in a dose-dependent inhibition of growth. Cytotoxic activity of GnRH-PAP was dependent on the number of GnRH receptors expressed on the surface of the cell lines (r2 = 0.871). In contrast, GnRH-PAP did not alter growth of CHO cells which did not express GnRH receptors. Moreover, the cytotoxic activity of GnRH-PAP could be partially inhibited by addition of excess GnRH analog. Neither free PAP nor GnRH analog alone affected proliferation of these cells. To determine the length of time that cells must be exposed to GnRH-PAP to completely inhibit proliferation, cells were treated at the beginning of a 7d incubation with GnRH-PAP for 1,6,24,48, 72, or 96h. Growth was completely inhibited in cells exposed to GnRH-PAP for 72h or longer. These results suggest that GnRH or its analogs can be used to specifically deliver toxin molecules to cells that express GnRH receptors on their surfaces. The result showed that the cytotoxicity of GnRH-RNase conjugates on cell lines expressing GnRH receptors was very low. This may be due to the presence of an endogenous RNase inhibitor in most cells. Since the efficiency of induction of apoptosis may have direct effects on the therapeutic usefulness of GnRH-toxin conjugates, the ability of GnRH-PAP conjugates to induce apoptosis of αT3-1 ceils was evaluated. The result showed for the first time that GnRH-PAP conjugates induced apoptosis after treatment of GnRH-PAP conjugates at 3h or longer. The result also showed that GnRH-PAP conjugates not only inhibit cell division but also induce cell death. Thus, a new class of biomedicines that act as hormonotoxins against cells expressing GnRH receptors provides a novel approach for inhibiting reproduction and treating cancers which are dependent on reproductive hormones.
Keywords: anatomy and physiology; animals; molecular biology